2022
DOI: 10.3390/axioms11060258
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Interval-Valued Intuitionistic Fuzzy Aczel–Alsina Geometric Aggregation Operators and Their Application to Multiple Attribute Decision-Making

Abstract: When dealing with the haziness that is intrinsic in decision analysis-driven decision making procedures, interval-valued intuitionistic fuzzy sets (IVIFSs) can be quite effective. Our approach to solving the multiple attribute decision making (MADM) difficulties, where all of the evidence provided by the decision-makers is demonstrated as interval-valued intuitionistic fuzzy (IVIF) decision matrices, in which all of the components are distinguished by an IVIF number (IVIFN), is based on Aczel–Alsina operationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Proof. By mathematical induction, we can prove that, Equation (30) holds for all positive integer n. First, we show that Equation (22) holds for n = 2, since…”
Section: Theorem 22mentioning
confidence: 94%
See 1 more Smart Citation
“…Proof. By mathematical induction, we can prove that, Equation (30) holds for all positive integer n. First, we show that Equation (22) holds for n = 2, since…”
Section: Theorem 22mentioning
confidence: 94%
“…Senapati et al introduced the IF Aczel-Alsina weighted averaging (IFAAWA) operator, the IF Aczel-Alsina orders weighted averaging (IFAAOWA) operator, and the IF Aczel-Alsina hybrid averaging (IFAAHA) operator. Senapati et al [29,30] developed interval-valued intuitionistic fuzzy aggregation operators, such as the IVIF Aczel-Alsina weighted averaging/geometric operator, the IVIF Aczel-Alsina order weighted averaging/geometric operator, and the IVIF Aczel-Alsina hybrid averaging/geometric operator and built up several features of such operators. Senapati [31] also defined picture fuzzy aggregation operator such as the PF Aczel-Alsina weighted average (PFAAWA) operator, the PF Aczel-Alsina order weighted average (PFAAOWA) operator, and the PF Aczel-Alsina hybrid average (PFAAHA) operator with their properties.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the Aczel-Alsina triangular norm (AA t-norm), Wang et al [49] devised a score level hybrid method. In recent times, Senapati et al [42][43][44][45] have developed ''(interval-valued) intuitionistic fuzzy Aczel-Alsina aggregation operators'' and implemented them to MADM technique.…”
Section: Research Gap and Motivation Of The Studymentioning
confidence: 99%
“…Many researchers used AAΤΝ and ΤCΝ and concluded that these norms and conorms give better results due to their parameters. Senapati et al [23][24][25][26][27][28][29][30] recognized the IF, IVIF, HF, PF, IVPF, and linguistic IF aggregation operators based on the AA-ΤΝ and AA-ΤCΝ by using the MADM challenges. Hussain et al [31] used the AA aggregation operators on TSFSs.…”
Section: Research Gap and Motivation Of The Study Atanassovmentioning
confidence: 99%